Comparison of two strategies for the management of postoperative recurrence in Crohn's disease patients with one clinical risk factor: A multicentre IG‐IBD study. Issue 3 (21st March 2023) - Dragoni, Gabriele; Castiglione, Fabiana; Bezzio, Cristina; Pugliese, Daniela; Spagnuolo, Rocco; Viola, Anna; Cocomazzi, Francesco; Aratari, Annalisa; Savarino, Edoardo Vincenzo; Balestrieri, Paola; Onali, Sara; Viganò, Chiara; et al.
Abstract: Background: The management of postoperative recurrence (POR) in Crohn's disease (CD) after ileo‐colonic resection is a highly debated topic. Prophylactic immunosuppression after surgery is currently recommended in the presence of at least one clinical risk factor. Objective: Our aim was to determine whether early immunosuppression can be avoided and guided by endoscopy in CD patients with only one risk factor. Methods: CD patients with only one risk factor for POR, including previous intestinal resection, extensive small intestine resection (>50 cm), fistulising phenotype, history of perianal disease, and active smoking, were retrospectively included. Two groups were formed based on whether immunosuppression was started immediately after surgery ("prophylaxis group") or guided by endoscopy ("endoscopy‐driven group"). Primary endpoints were rates of any endoscopic recurrence (Rutgeerts ≥ i2a) and severe endoscopic recurrence (i4) within 12 months after surgery. Secondary outcomes were clinical recurrence rates at 6, 12 and 24 months after surgery. Results: A total of 195 patients were enroled, of whom 61 (31.3%) received immunoprophylaxis. No differences between immunoprophylaxis and the endoscopy‐driven approach were found regarding any endoscopic recurrence (36.1% vs. 45.5%, respectively, p = 0.10) and severe endoscopic recurrence (9.8% vs. 15.7%, respectively, p = 0.15) at the first endoscopic evaluation. Clinical recurrence rates were also not statistically different ( p = 0.43, p = 0.09, and p = 0.63 at 6, 12, and 24 months, respectively). Conclusions: In operated CD patients with only one risk factor for POR, immediate immunoprophylaxis does not decrease the rate of early clinical and endoscopic recurrence. Prospective studies are needed to confirm our results. Abstract :